2011
DOI: 10.3109/10673229.2011.586550
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids as Predictors of Treatment Response in Depression

Abstract: The glucocorticoid system is potentially of great use in predicting antidepressant response. New combinations of biomarkers including these measures should be tested to develop clinically relevant predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 153 publications
(114 reference statements)
1
14
0
Order By: Relevance
“…Moreover, they also found associations of the same marker with the antidepressant response, faster response to antidepressant treatment, lower activity of the HPA axis during a depressive episode, and a higher recurrence of depressive episodes in their lifetime, with an over-representation of T/T homozygotes among the responders [93]. These results have been replicated in some studies [81], but not in others [94]. The causes of this discrepancy may reside in genetic differences in the ethnic populations tested, lifetime recurrence of depressive episodes, or differences in the phenotypes and drugs used.…”
Section: Genetic Differences Influence Responses To Antidepressantsmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, they also found associations of the same marker with the antidepressant response, faster response to antidepressant treatment, lower activity of the HPA axis during a depressive episode, and a higher recurrence of depressive episodes in their lifetime, with an over-representation of T/T homozygotes among the responders [93]. These results have been replicated in some studies [81], but not in others [94]. The causes of this discrepancy may reside in genetic differences in the ethnic populations tested, lifetime recurrence of depressive episodes, or differences in the phenotypes and drugs used.…”
Section: Genetic Differences Influence Responses To Antidepressantsmentioning
confidence: 85%
“…Although the most common antidepressants target the monoaminergic systems, they also decrease HPA axis hyperactivity, alleviating depressive symptoms (reviewed in [81]). The effects of antidepressants on monoamine levels are exerted rapidly, within few hours; however, the therapeutic response is only observed several weeks after the initiation of treatment.…”
Section: Genetic Differences Influence Responses To Antidepressantsmentioning
confidence: 99%
“…The most common antidepressants currently available, including fluoxetine (FLX), are targeted to the monoaminergic systems [5,6]. The effects of antidepressants on monoamines are observed within a few hours.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these studies have been conducted in the context of antidepressant medications (Young et al, 2004; Horstmann and Binder, 2011), but several studies have also observed an association between pretreatment cortisol levels and posttreatment outcomes following a psychosocial intervention (Bockting et al, 2006; Jason et al, 2008; Yehuda et al, 2009; Otto et al, 2010; Bockting et al, 2012). In particular, some preliminary evidence suggests that hypercortisolism predicts poorer response to CBT (Thase et al, 1993; Thase et al, 1996; Thase and Friedman, 1999).…”
Section: Introductionmentioning
confidence: 99%